The geometry of Karoo dolerite dykes and saucers in the Highveld Coalfield : constraints on emplacement processes of mafic magmas in the shallow crust - Coetzee, Andre (Stellenbosch : Stellenbosch University, 2016)
Thesis (MSc)--Stellenbosch University, 2016.